Exploration of High-Grade Transformation and Postoperative Radiotherapy on Prognostic Analysis for Primary Adenoid Cystic Carcinoma of the Head and Neck - Zhu, Yuelu; Zhu, Xinyi; Xue, Xuemin; Zhang, Ye; Hu, Chunfang; Liu, Wenchao; Lu, Haizhen (Frontiers in Oncology, 2021)
Background: In spite that adenoid cystic carcinoma (ACC) with cribriform or tubular components is recognized as indolent malignancy, ACC with solid or rarely high grade transformation (HGT) components is considered as more aggressive disease. Since the amount of solid components is difficult to be measured objectively, and the role of HGT in the current grading system remains unclear, the prognostic influence of tumor grading remains controversial. In addition, being confronted with the high rate of nerve invasion and close surgical margin in ACC of head and neck (ACCHN), postoperative radiotherapy (PORT) is proved effective to local control. However it still remains to be explored that whether PORT could benefit ACC patients in terms of survival, especially with HGT. Methods: A series of 73 surgically treated primary ACCHN cases were retrospectively accessed. Immunohistochemical staining was performed to observe the biphasic ductal-myoepithelial differentiation and to identify the HGT components of ACC for tumor grading. The correlation between tumor grading and clinicopathological characteristics was analyzed. Univariate and multivariate prognostic analysis were performed for progression-free-survival (PFS) and overall-survival (OS). Results: There were 47 grade Ⅰ-Ⅱ ACC cases and 26 grade Ⅲ cases. Among the grade Ⅲ cases, 14 with loss of biphasic ductal-myoepithelial differentiation identified by immunostaining were classified as HGT, which could be distinguished from conventional grade Ⅲ cases. These HGT cases were correlated with high propensity of lymph node metastases and more advanced stage. On univariate analysis, tumor grading, perineurual invasion, T stage, stage group and PORT were predictors for PFS, whereas tumor grading, margin status and PORT were predictors for OS. However, only tumor grading and PORT were both independent predictors for PFS and OS. The HGT patients had significant worse prognosis compared to the conventional ACC patients. In addition, disease progression tended to occur in the younger patients. Among the HGT patients, those who received PORT had longer median survival time compared to those who did not. Conclusion: HGT ACC identified by loss of biphasic differentiation should be considered in tumor grading. Tumor grading and PORT were independent predictors for disease progression and overall survival in surgically treated ACCHN patients.